Gastrointestinal basidiobolomycosis in pediatric age group: A single-center experience [Case Series] - Madani Essa (Elsevier, 2022)
Background: Basidiobolomycosis is a rare tropical fungal infection that affects mainly the skin. Gastrointestinal basidiobolomycosis (GIB) is extremely rare, especially in the pediatric age group with no history of immune deficiency diseases. Patients and methods: Our patients have been diagnosed and managed between 2016 and 2019; diagnoses have been confirmed by histopathology. Results: Six children were analyzed: 1 female and 5 males. Their age range was 15 months to 6 years of age. All patients came from Jazan governance, southwestern Saudi Arabia. None of the patients had a history of immune deficiency diseases. They all had a high level of eosinophil, erythrocyte sedimentation rate (ESR), and C-reactive protein. Three of them were diagnosed initially with GIT mass, 2 with acute appendicitis, and one with intussusception. Most of them were subjected to surgical procedures before definitive diagnosis: 2 had mass resection and 4 had a stoma. Only one case was diagnosed by simple biopsy, with no laparotomy, which reflects the difficulty of direct diagnosis of disease. All patients were managed properly post definitive diagnoses with antifungal and recovered completely. Conclusion: GIB is generally a lethal fungal infection, which can affect even immunocompetent individuals. Patients with GIB can present with variant complaints: constipation, vomiting, abdominal distention, or simply a palpable mass. Proper investigation, including complete blood count, ESR, and radiological examination, can prevent unnecessary surgery and catastrophic surgical management. Pediatric patients can recover completely after receiving antifungals if diagnosed early.